The Fermented Soy Product ImmuBalanceTM Suppresses Airway Inflammation in a Murine Model of Asthma - Kadotani, Hideaki; Asai, Kazuhisa; Miyamoto, Atsushi; Iwasaki, Kohei; Kawai, Takahiro; Nishimura, Misako; Tohda, Mitsunori; Okamoto, Atsuko; Sato, Kanako; Yamada, Kazuhiro; Ijiri, Naoki; Watanabe, Tetsuya; et al. (Nutrients, 2021)
The fermented soy product ImmuBalance contains many active ingredients and its beneficial effects on some allergic diseases have been reported. We hypothesized that ImmuBalance could have potential effects on airway inflammation in a murine model of asthma. Mice sensitized and challenged with ovalbumin developed airway inflammation. Bronchoalveolar lavage fluid was assessed for inflammatory cell counts and levels of cytokines. Lung tissues were examined for cell infiltration and mucus hypersecretion. Oral administration of ImmuBalance significantly inhibited ovalbumin-induced eosinophilic inflammation and decreased Th2 cytokine levels in bronchoalveolar lavage fluid (p < 0.05). In addition, lung histological analysis showed that ImmuBalance inhibited inflammatory cell infiltration and airway mucus production. Our findings suggest that supplementation with ImmuBalance may provide a novel strategy for the prevention or treatment of allergic airway inflammation.